2021
DOI: 10.3390/ma14154222
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Supervised Machine Learning Algorithms for Predicting the Compressive Strength of Concrete at High Temperature

Abstract: High temperature severely affects the nature of the ingredients used to produce concrete, which in turn reduces the strength properties of the concrete. It is a difficult and time-consuming task to achieve the desired compressive strength of concrete. However, the application of supervised machine learning (ML) approaches makes it possible to initially predict the targeted result with high accuracy. This study presents the use of a decision tree (DT), an artificial neural network (ANN), bagging, and gradient b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(48 citation statements)
references
References 74 publications
0
41
0
Order By: Relevance
“…This investigation is concerned with the influence of input parameters on forecasting the CS of SCM-based concrete. The input parameters have a considerable impact on the outcome projection [ 46 ]. The influence of each input parameter on the CS prediction of concrete is depicted in Figure 11 .…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This investigation is concerned with the influence of input parameters on forecasting the CS of SCM-based concrete. The input parameters have a considerable impact on the outcome projection [ 46 ]. The influence of each input parameter on the CS prediction of concrete is depicted in Figure 11 .…”
Section: Results and Analysismentioning
confidence: 99%
“…This also supports the higher accuracy of the bagging technique for the prediction of the results. The literature also indicated that bagging models produce more accurate outcomes than other ML approaches [ 29 , 46 ]. Moreover, a sensitivity analysis was performed to determine the impact of each input parameter on the prediction of the CS of SCM-based concrete.…”
Section: Discussionmentioning
confidence: 99%
“…In general, two methods of ML are used for modeling and predicting. Firstly, there is the traditional solution built on a single in-dependent paradigm, while secondly, there are collective learning algorithms, including boosting, bagging, and random forests created on many components of the data-base [ 55 ]. Individual ML models have weak learners who tend to produce overfitting of the data.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this evaluation is to determine the impact of input variables on forecasting the C-S of HPC. The input parameters have a considerable influence on the projected outcome [24]. Figure 12 illustrates the effect of each input parameter on the C-S prediction of HPC.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In recent years, machine learning (ML) algorithms have demonstrated significant potential for forecasting cementitious material properties [22][23][24][25][26][27][28]. Among the numerous machine learning methods, support vector regression (SVR) and artificial neural network (ANN) methods have been widely utilized to predict concrete parameters such as compressive strength (C-S) [29], split-tensile strength, elastic modulus, and so on [30][31][32].…”
Section: Introductionmentioning
confidence: 99%